Changes in Pharyngeal Airway Space and Craniocervical Angle after Anterior Bimaxillary Subapical Osteotomy. (11th August 2021) - Cheng, Jung-Hsuan; Chen, Chun-Feng; Chen, Ping-Ho; Hsu, Kun-Jung; Chen, Han-Sheng; Chen, Chun-Ming
Abstract : Purpose . This study explored the effects of genioplasty (Gep) and anterior subapical osteotomy of the maxilla and mandible (ASOMx+ASOMd) on the pharyngeal airway dimensions of patients with bimaxillary protrusion (BiP). Method . Thirty-two patients were divided into 2 groups. Group 1 received ASOMx+ASOMd, and group 2 received ASOMx+ASOMd+Gep. The cephalograms of the patients were collected before surgery and 2 months after surgery. Changes in the landmarks, related cephalometric angles (gonial, SN-GoGn, Y -axis, and SN-C2C4 angles), and 2 pharyngeal airway dimensions (uvulo-pharyngeal airway [UOP] and tongue–pharyngeal airway [TOP]) were analyzed. Results . Before surgery, the parameters (incisor superius, incisor inferius, menton, most superior and anterior point of the hyoid bone, tip of the uvula, inferoanterior point on the second cervical vertebra, and inferoanterior point on the fourth cervical vertebra) and measured angles (SNA, SNB, ANB, gonial, SN-GoGn, Y -axis, and C4C2-SN) of both groups showed no significant differences. Following ASOMx, the patients in groups 1 and 2 exhibited a setback by 7.0 and 6.6 mm, respectively. After ASOMd, groups 1 and 2 exhibited 4.9 and 5.3 mm setbacks, respectively. No significant difference in the amount of setback was observed between groups 1 and 2. The postoperative horizontal and vertical positions of Me in group 2 were significantly forward by 6.1 mm and upward by 1.5 mm, respectively. Regarding pharyngeal airway dimensions, TOP was decreased in group 1 (1.7 mm) and group 2 (1.3 mm). In the postoperative Pearson correlation coefficient test, the horizontal and vertical positions of Me showed no significant correlation with TOP in both groups. Therefore, Gep did not prevent the reduction of TOP in group 2. Conclusion . After bimaxillary anterior subapical osteotomy, the TOP of patients with BiP was decreased, and this situation was unavoidable, regardless of whether Gep was performed.